Prediction of the solubility of aromatic components of wine in carbon dioxide - Domingos Barbosa (2004)
The possibility of using group contribution methods to predict the solubility of the most important families of aromatic compounds of wine-alcohols, esters and aldehydes-in carbon dioxide (CO2) is analyzed in this work by comparing the results obtained with three different predictive methods, which couple equations of state and mixing rules based on the concept of the excess Gibbs free energy. The methods studied are the Predictive Soave-Redlich-Kwong (PSRK), the Linear Combination of the Vidal and Michelsen mixing rules (LCVM) and the Wong-Sandler mixing rule (WS). In all these models the excess Gibbs free energy is calculated by the UNIFAC method. For the WS mixing rule, interaction parameters between the groups CO2/CH2, CO2/OH, CO2/CCOO and CO2/CHO are obtained. For the LCVM mixing rule, interaction parameters are calculated for the groups CO2/CHO, and revised values for the groups CO2/OH are suggested. Finally, for the PSRK mixing rule, revised values are proposed for the interaction parameters between the groups CO2/OH and CO2/CHO. The results of this work show that the PSRK is the method that best predicts the phase equilibria for the systems studied, with a quadratic mean deviation lower than 5.5%.